(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article deals the semantic features of full interlingual homonyms in Ukrainian and Belarusian languages. In particular, it reveals the meaning of “interlingual homonymy,” clarifies the criteria for distinguishing interlingual homonyms and paronyms, outlines the principles of classification of interlingual homonyms in modern linguistics, and analyzes the semantic relations between Ukrainian and Belarusian lexemes connected by full interlingual homonymy. Interlingual homonyms pose great difficulties in the practice of translation and lexicographic work or in the teaching of foreign languages. Inaccurate choice of correspondent in the process of communication or translation can lead to a change in stylistic color and a loss of semantics of the whole phrase. The described mistakes are made by both people who have just started learning a foreign language, and experts who seem to be confident in using a foreign language. By interlingual homonyms we mean multilingual words that coincide in form orally, in writing or within regular correspondences (phonetic, graphic, orthographic, accentual, morphemic and derivational) existing between the compared linguistic systems, and completely or partially differing in meaning. Based on the logical scheme of formal and notional correspondence, the relationship between full interlingual homonyms can be characterized as a semantic exception. Analysis of the semantic features of full Ukrainian-Belarusian interlingual homonyms showed that their appearance is caused by the uneven development of semantic structures of etymologically identical lexemes, or the accidental coincidence of word forms of different origins, or the influence of intralingual homonymy. The article deals with the peculiarities of interlingual homonyms in closely related languages and analyzes the semantic relations between Ukrainian and Belarusian lexemes characterized by full (complete) interlingual homonymy.